Evaluation by obstetric care providers of simulated postpartum blood loss using a collector bag: a French prospective study. (1st November 2016) - Legendre, Guillaume; Richard, Marion; Brun, Stéphanie; Chancerel, Marion; Matuszewski, Sarah; Sentilhes, Loic
Abstract: Objective : Postpartum hemorrhage (PPH) is one of the most common causes of mortality in obstetrics worldwide. Accuracy in the estimated blood loss is a priority in determining appropriate treatment. The aim of this study was to evaluate the accuracy of estimating blood loss by obstetrics care providers during simulated training sessions. Method : A prospective study occurred in 2013 in a maternity ward at a teaching hospital. Simulation training sessions recreated a vaginal delivery in which six different scenarios were presented and proposed to each participant for them to estimate the blood loss (from 350 ml to 2500 ml) while using a collector bag graduated every 100 ml from 0 ml to 1500 ml. The primary endpoint was to determine if participants could accurately evaluate blood loss within a 20% error margin. Results : About 90.7% of the medical staff participated. Ninety-three to 98% of the participants were accurate in their answer depending on which volume they had to estimate. For the lowest volume (350 ml), there was 11.1% overestimation between the estimated volume of blood loss (EBV) and the real volume of blood loss (RBV). However, there was an 8.8% underestimation found for the highest volume. Conclusion : The accuracy of the estimated blood loss for the obstetrical medical staff, using the collector bag, is more than 96%.